2016
DOI: 10.1073/pnas.1600511113
|View full text |Cite
|
Sign up to set email alerts
|

High Elmo1 expression aggravates and low Elmo1 expression prevents diabetic nephropathy

Abstract: Human genome-wide association studies have demonstrated that polymorphisms in the engulfment and cell motility protein 1 gene (ELMO1) are strongly associated with susceptibility to diabetic nephropathy. However, proof of causation is lacking. To test whether modest changes in its expression alter the severity of the renal phenotype in diabetic mice, we have generated mice that are type 1 diabetic because they have the Ins2Akita gene, and also have genetically graded expression of Elmo1 in all tissues ranging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 27 publications
(24 reference statements)
1
52
0
Order By: Relevance
“…We found that these patients, that we analysed, displayed an unaltered expression of ELMO1 within the renal parenchyma. This is in accordance with our research conducted on zebrafish embryos, but is in contrast to a recent published study which suggested that low ELMO1 expression prevents diabetic nephropathy development in mice23. It is common knowledge that no animal model completely adheres to the pathogenic mechanisms of human diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 92%
“…We found that these patients, that we analysed, displayed an unaltered expression of ELMO1 within the renal parenchyma. This is in accordance with our research conducted on zebrafish embryos, but is in contrast to a recent published study which suggested that low ELMO1 expression prevents diabetic nephropathy development in mice23. It is common knowledge that no animal model completely adheres to the pathogenic mechanisms of human diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 92%
“…Functional studies have found that a high level of Elmo1 expression aggravated the progression of DN and vice versa. The severity of renal fibrosis, the amount of urinary albumin excretion and changes in the ultrastructure of the glomerular basement membrane in Akita diabetic mice paralleled the genetic levels of ELMO1 [50]. Possible mechanisms by which ELMO1 is involved in the pathogenesis of DN include: (1) ELMO1 and oxidative stress: ELMO1 promotes the production of reactive oxygen species by activating Rac and increasing the expression of NAD(P)H oxidase, thereby increasing oxidative stress in the kidney, leading to renal oxidative damage [50]; (2) ELMO1 and renal fibrosis: increased expression of ELMO1 promotes the expression of fibrogenic genes (such as TGF-β1 and genes encoding type 1 collagen and fibronectin, etc.)…”
Section: Inflammation and Oxidative Stress-related Genesmentioning
confidence: 99%
“…The severity of renal fibrosis, the amount of urinary albumin excretion and changes in the ultrastructure of the glomerular basement membrane in Akita diabetic mice paralleled the genetic levels of ELMO1 [50]. Possible mechanisms by which ELMO1 is involved in the pathogenesis of DN include: (1) ELMO1 and oxidative stress: ELMO1 promotes the production of reactive oxygen species by activating Rac and increasing the expression of NAD(P)H oxidase, thereby increasing oxidative stress in the kidney, leading to renal oxidative damage [50]; (2) ELMO1 and renal fibrosis: increased expression of ELMO1 promotes the expression of fibrogenic genes (such as TGF-β1 and genes encoding type 1 collagen and fibronectin, etc.) and inhibits the expression of anti-fibrotic genes (such as matrix metalloproteinase genes), leading to excessive accumulation of extracellular matrix proteins and thickening of the glomerular basement membrane and consequently resulting in the initiation and progression of diabetic glomerulosclerosis [46].…”
Section: Inflammation and Oxidative Stress-related Genesmentioning
confidence: 99%
“…For example, removal of the ARE from the TNFα mRNA in mice resulted in a severe TNFα overproduction syndrome and inflammatory bowel disease [32]. Smithies and colleagues [33, 34] achieved various levels of expression of their mRNAs and proteins of interest by inserting either labile or stable regions into the 3’UTRs of their target genes. Deletion of an AU-rich region of the interferon gamma mRNA 3’UTR stabilized this transcript, and resulted in increased secretion of interferon in the mouse [35].…”
Section: Ttp Gain Of Function Experiments Demonstrate a Protective Romentioning
confidence: 99%